La responsabilité civile des professionnels réunis en société de droit ou de fait - Frenette, François (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
The rules of partnership are not without incidence upon the delictual and contractual responsibility of professionals practicing in common. The influence of such rules are here examined in relation, first of all, to the number of partners that can be personally held liable for professional faults committed by one or several members of the group and, finally, to the extent of their liability in such case.